A Silicon Nanomembrane Detector for Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) of Large Proteins - Jonghoo Park; Robert H. Blick (Sensors, 2013)
We describe a MALDI-TOF ion detector based on freestanding silicon nanomembrane technology. The detector is tested in a commercial MALDI-TOF mass spectrometer with equimolar mixtures of proteins. The operating principle of the nanomembrane detector is based on phonon-assisted field emission from these silicon nanomembranes, in which impinging ion packets excite electrons in the nanomembrane to higher energy states. Thereby the electrons can overcome the vacuum barrier and escape from the surface of the nanomembrane via field emission. Ion detection is demonstrated of apomyoglobin (16,952 Da), aldolase (39,212 Da), bovine serum albumin (66,430 Da), and their equimolar mixtures. In addition to the three intact ions, a large number of fragment ions are also revealed by the silicon nanomembrane detector, which are not observable with conventional detectors.